Non-technological innovation: current issues and perspectives - Pereira, Cristina Saraiva (2013)
Innovation can be considered to be a complex phenomenon including technical and non-technical aspects. A remarkable increase in the interdisciplinary attention devoted to innovation has been noticed over the recent decades but the formal technological and economic aspects of innovation have received much more attention and have been taken into account in a far greater number of analyses, despite the great importance of the non-technological dimension of innovation. This paper attempts a review on the important subject of nontechnological innovation. The main ideas on the non-technological dimension of innovation research will be highlighted, followed by an attempt to integrate diverse and disparate perspectives on the subject, to present evidence on possible generalizations and to discuss eventual research gaps and opportunities for further studies. The relationship between technological and non-technological innovation is complex and not fully understood. Among several aspects that will be covered in this paper, two specific ones will receive special attention in this brief analysis: the evidence on the impacts of non-technological innovation, and the measurements efforts that have been made concerning this phenomenon.